Bivalirudin as an adjunctive anticoagulant to heparin in the treatment of heparin resistance during cardiopulmonary bypass-assisted cardiac surgery. (April 2016) - McNair, E; Marcoux, J-A; Bally, C; Gamble, J; Thomson, D
Heparin resistance (unresponsiveness to heparin) is characterized by the inability to reach acceptable activated clotting time values following a calculated dose of heparin. Up to 20% of the patients undergoing cardiothoracic surgery with cardiopulmonary bypass using unfractionated heparin (UFH) for anticoagulation experience heparin resistance. Although UFH has been the "gold standard" for anticoagulation, it is not without its limitations. It is contraindicated in patients with confirmed heparin-induced thrombocytopenia (HIT) and heparin or protamine allergy. The safety and efficacy of the use of the direct thrombin inhibitor bivalirudin for anticoagulation during cardiac surgery has been reported. However, there have been no reports on the treatment of heparin resistance with bivalirudin during CPB. In this review, we report the favorable outcome of our single-center experience with the alternative use of bivalirudin in the management of anticoagulation of heparin unresponsive patients undergoing coronary artery bypass graft surgery.